WOOD THE POTENTIAL RESOURCE OF COMPLEX USE OF LIGNIN - Pujate, Agnese; Noviks, Gotfrīds (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2019)
The aim of the work is to investigate the use of existing wood waste, the most effective method of obtaining lignin and to create composite material made from renewable natural resources. The work looked at the current wider use of wood resources - construction, energy and chemical processing. The current waste from the use of wood - lignin is investigated. And the complex and rational use of this waste without waste. Experimentally, lignin was obtained with two methods, alkali and acid, from different Latvian tree species. Experimentally obtained composite samples with different compositions - alkali / acid lignin (binder) and leafy tree ash / chips (filler). Also, composite materials are considered at different proportions, where the percentage of both binders and fillers changes. Experimental samples were pressed at different temperatures.